Preparative production of an enantiomeric pair by engineered polyketide synthases. Issue 70 (11th August 2021) - Miyazawa, Takeshi; Fitzgerald, Brendan J.; Keatinge-Clay, Adrian T.
Abstract : Modules from the pikromycin synthase were recombined into engineered synthases that furnish an enantiomeric pair of 2-stereocenter triketide lactones at >99% ee with yields up to 0.39 g per liter of E. coli K207-3 in shake flasks. Abstract : Using the updated module boundary of polyketide assembly lines, modules from the pikromycin synthase were recombined into engineered synthases that furnish an enantiomeric pair of 2-stereocenter triketide lactones at >99% ee with yields up to 0.39 g per liter of E. coli K207-3 in shake flasks.